ESL learners' use of online metacognitive reading strategies: an exploratory study / Nursyazwani Mohd Kamal - Mohd Kamal, Nursyazwani (Faculty of Education, 2010)
This study investigated the metacognitive awareness and online reading strategies employed by Form Four ESL learners' of a secondary school in relation to language proficiency. Specifically, it examined the types and frequency of reading strategies used by the high and low language proficiency students and the differences between them. Additionally, the study attempted to find out the relationship between the ESL learners' overall language proficiency performance and their frequency of use of the overall and three sub-categories of reading strategies, namely global, problem-solving and support strategies. The research design was a cross-sectional survey research which used the Anderson (2003) Online Survey of Reading Strategies (OSORS). The independent variable was the language proficiency of the ESL learners and the dependent variable was the metacognitive awareness of the ESL learners measured in terms of their ratings of the three sub-categories of reading strategies. Data obtained from the questionnaire were analyzed using One-way ANOVA, independent sample t-test and Pearson's Product Moment Correlation Coefficient. The findings of the study revealed that the high language proficiency students were moderate reading strategy users. High language proficiency students used the global, problem-solving, and support strategies with somewhat similar moderate frequency. However, the low proficiency students used the problem-solving and support strategies with higher frequency than the global strategies. High proficiency students used overall, global and problem solving strategies more frequently than the low proficiency students. However, support strategies were used with somewhat similar frequency by both high proficiency and low proficiency students. Moreover, there was a positive significant relationship between the ESL learners' overall language proficiency performance and their frequency of use of global and problem solving strategies. However, there was a negative significant relationship between the ESL learners' overall language proficiency performance and their frequency of use in support strategies. Pedagogical implications are offered along with suggestions for further research.